The establishment of apple orchards as temperate forest garden systems and their impact on indigenous bacterial and fungal population abundance in Southern Ontario, Canada. Issue 2 (13th July 2016) - Wartman, P.C.; Dunfield, K.E.; Khosla, K.; Loucks, C.; Van Acker, R.C.; Martin, R.C.
Abstract: This research investigated soil microbial abundances affected by different ground management systems in establishing apple ( Malus domestica cv. Idared, M9) orchards in Ontario, Canada. Four treatments, including forest garden systems with and without compost (FGSC and FGS), and grass understory systems with and without compost (GC and G), were assessed over two establishment years for gene copy abundance of soil arbuscular mycorrhizal (AM) fungi, total fungi and total bacteria using quantitative real-time polymerase chain reactions. Time had a greater effect on all three soil microbial abundances, with total bacterial and AM fungi decreasing and total fungal abundance increasing from spring 2013 to fall 2014. The changes were greatest between the sampling dates of fall 2013 and spring 2014, which is 1 yr after the establishment of the experimental apple plots. There were no significant differences in soil microbial abundances between treatments at any specific sampling date. Apple tree trunk circumference was greatest for FGSC and FGS after 2 yr, but no significant differences in GC and G treatments. In the last sampling period, fall 2014, FGSC plots had significantly greater trunk circumferences compared with G plots. Soil chemical properties neither changed over the 2 yr, nor did they differ between treatments at any one sampling time. We conclude that the apple-based FGS treatments can benefit apple tree growth and there is a basis for future research to explore specific plant–plant, plant–microbe and microbe–microbe relations in FGSs.